ARUS SELATAN JAWA - Dewi Surinati; Jaka Harry Mulyanto Wijaya (Pusat Penelitian Oseanografi LIPI, 2017)
SOUTH JAVA CURRENT. Indian Ocean is influenced by the monsoon cycle. Monsoon cycle that occurs in the Indian Ocean influences the current patterns. Since a very strong westerlies occurs in The Tropical Convergence Zone (TCZ) at the equator, wyrtki jet is formed in the 40° - 80° W Indian Ocean on a transitional season. Its branchs are possibly formed when the wyrtki jet is in the equatorial west coast of Sumatra to the north and south along the western coast of Sumatra which eventually creates South Java Current (SJC). SJC flows southeastward during December–April and northwestward during June–October, when it is associated with coastal upwelling. SJC develop upwelling on a seasonal basis.